The Land of Gold : Post-Conflict Recovery and Cultural Revival in Independent Timor-Leste - Bovensiepen, Judith M. (Book collections on Project MUSE., 2015)
"In the village of Funar, located in the central highlands of Timor-Leste, the disturbing events of the twenty-four-year-long Indonesian occupation are rarely articulated in narratives of suffering. Instead, the highlanders emphasize the significance of their return to the sacred land of the ancestors, a place where "gold" is abundant and life is thought to originate. On one hand, this collective amnesia is due to villagers' exclusion from contemporary nation-building processes, which bestow recognition only on those who actively participated in the resistance struggle against Indonesia. On the other hand, the cultural revival and the privileging of the ancestral landscape and traditions over narratives of suffering derive from a particular understanding of how human subjects are constituted. Before life and after death, humans and the land are composed of the same substance; only during life are they separated. To recover from the forced dislocation the highlanders experienced under the Indonesian occupation, they thus seek to reestablish a mythical, primordial unity with the land by reinvigorating ancestral practices. Never leaving out of sight the intense political and emotional dilemmas imposed by the past on people's daily lives, The Land of Gold seeks to go beyond prevailing theories of post-conflict reconstruction that prioritize human relationships. Instead, it explores the significance of people's affective and ritual engagement with the environment and with their ancestors as survivors come to terms with the disruptive events of the past."--Page 4 of cover